Collection and DNA Detection of Dirofilaria immitis (Rhabditida Onchocercidae), Using a Novel Primer Set, in Wild-Caught Mosquitoes From Gainesville, FL. Issue 3 (8th December 2020) - Holderman, Chris; Abruzzo, Nicole O; Abdelsamad, Noor A; Kaufman, Phillip E; DiGennaro, Peter M
Abstract: Dirofilaria immitis, the causative agent of dog heartworm disease, is an important cause of canine morbidity and mortality, expensive to treat, and severe infections are often fatal. Much is known about the pathogen in the canine host, yet little is known on the basic ecology of the nematode in the mosquito vector. Thus, to evaluate the effectiveness of collection techniques on ability to capture dog heartworm-infected mosquitoes (Diptera Culicidae), we conducted a field study spanning 111 wk. Four methods were used: two aspirators types, sweep netting, and a CDC trap. All sites had canines present in either residential yards ( n = 4) or dog kennel facilities ( n = 3). Collected mosquitoes were sorted by site, trap, species, and date, then pooled into groups of up to 25 individuals. Mosquito head and thorax pools were extracted for DNA, that was screened using currently available protocols. These protocols were found unreliable; thus, we developed a novel qPCR primer and probe set. Using this method, the original samples were re-assayed and provided 494 positive pools. Approximately 10% of positive samples were confirmed by Sanger sequencing. Twenty-two mosquito species tested positive for dog heartworm DNA, including a new association with Wyeomyia mitchellii (Theobald). Although Aedes atlanticus (Dyar and Knab), Anopheles crucians Wiedemann, and Culiseta melanura (Coquillett) composed nearly 36% of the total collection, these species represented 42% of the qPCR positive pools. Infection rates within commonly collected mosquitoes ranged up to 2.5%, with more rarely collected species ranging up to 14%. The CDC trap was the most effective collection method at trapping infected mosquitoes.